Local level institutional complementarities in contemporary China - Alexandre De Podestá Gomes (Revue de la Régulation)
This paper has the objective of bringing to light and comparing two different types of institutional arrangements existing in two different prefecture-level cities in China: Nanjing and Suzhou. Although both are considered affluent cities, and located in the same broad economic area, the Yangtze River Delta (YRD), and the same sub-provincial region, Southern Jiangsu, the cities present markedly distinct local institutional arrangements and accumulation regimes. The paper argues that the historical legacies of Nanjing and Suzhou have moulded the distinct institutional arrangements found in both cities, and that institutional path-dependences shaped the policies and strategies the cities decided to implement, eventually leading to distinct accumulation regimes. This study privileges a political economy definition of institutions (Amable, 2003; Boyer, 1988), and employs the concept of institutional complementarities (Amable, 2016; Aoki, 1994) in order to tackle the institutional arrangements of Nanjing and Suzhou. Initially, the paper introduces the debate on the nature of China’s state, arguing that the country is better characterized by its internal institutional heterogeneities, and that these heterogeneities often reveal themselves at subnational levels. Then the paper proceeds by presenting the analytical framework employed in this research and, after introducing the definitions of institutions and institutional complementarities, a comparison between Nanjing and Suzhou is presented. The final sections summarize the institutional characteristics and accumulation regimes found in both cities and conclude with the analysis.